Experimental study on surface wrinkling of silicon monoxide film on compliant substrate under thermally induced loads. (24th May 2017) - Li, Chuanwei; Kong, Yingxiao; Jiang, Wenchong; Wang, Zhiyong; Li, Linan; Wang, Shibin
Abstract: The wrinkling of a silicon monoxide thin film on a compliant poly(dimethylsiloxane) (PDMS) substrate structure was experimentally investigated in this study. The self-expansion effect of PDMS during film deposition was utilized to impose a pretensile strain on the structure through a specially made fixture. A laser scanning confocal microscope (LSCM) system with an in situ heating stage was employed for the real-time measurement. The Young's modulus of the silicon monoxide thin film as well as the PDMS substrate was measured on the basis of the elasticity theory. Moreover, the effects of temperature variations on geometric parameters in the postbuckling state, such as wavelength and amplitude, were analyzed. It was proved that wavelength is relatively immune to thermal loads, while amplitude is much more sensitive.